Flexible Learning Makes Online Studies Easy - The, Star (The Star, 2019)
Asia e University (AeU) offers a wide range of postgraduate degree programmes designed to develop students with skills to succeed in thier chosen fields. One of AeU's most sought-after prgrammes is the master of Education (MEd). This programme is designed to provide students with the knowledge and skills to be effective educators. It seeks to provide a theoretical perspective of educational practices in various areas of concentrations